2021
DOI: 10.3389/fpsyg.2021.691755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Factors Influencing Knowledge-Sharing Behavior of Students in Online Problem-Based Learning

Abstract: Adopting online problem-based learning (OPBL) to internship educational programs is an effective teaching method to stimulate self-directed and collaborative learning and knowledge-sharing behavior (KSB) of students. However, the OPBL collaboration experience is different from the traditional lecture-based learning experience for students. Integrating social identity theory and commitment-trust theory develops a formative research model that explains the KSB of students when using social media tools for the OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 64 publications
1
14
0
3
Order By: Relevance
“…According to H4, this study also found that kindergarten parental trust and parental relationship commitment played significant chain mediating roles in the relationship between parental satisfaction and parental loyalty, this was consistent with previous research findings according to that the chain meditation effect played a role in customers’ relationship and customers’ commitment ( Sanchez-Franco et al, 2009 ). In addition, similar to empirical findings, trust and relationship commitment have been shown to be key mediating factors ( Friman et al, 2002 ; Sue and Campbell, 2012 ; Wang and Lin, 2021 ). In other words, the KMV model can be applied to kindergarten parents, and trust and relationship commitment play a key mediating role between parental satisfaction and parental loyalty.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…According to H4, this study also found that kindergarten parental trust and parental relationship commitment played significant chain mediating roles in the relationship between parental satisfaction and parental loyalty, this was consistent with previous research findings according to that the chain meditation effect played a role in customers’ relationship and customers’ commitment ( Sanchez-Franco et al, 2009 ). In addition, similar to empirical findings, trust and relationship commitment have been shown to be key mediating factors ( Friman et al, 2002 ; Sue and Campbell, 2012 ; Wang and Lin, 2021 ). In other words, the KMV model can be applied to kindergarten parents, and trust and relationship commitment play a key mediating role between parental satisfaction and parental loyalty.…”
Section: Discussionsupporting
confidence: 67%
“…Trust and relationship commitment did facilitate collaborative relationships between librarians and teachers in teaching and research. Wang and Lin (2021) showed that the KMV model could also be applied to students in nursing and medical schools. Interpersonal trust and relationship commitment act as chain mediating roles between interpersonal relationship quality and knowledge sharing behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing knowledge management are divided into four parts, namely subject, object, organisational culture and information technology (Lin et al, 2008). It has been shown that knowledge sharing within various tyPractice Environment Scale of organisations through different means and processes have positive impacts on individuals and teams (Wang & Lin, 2021; Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the relationship between group members plays a vital role in creating interpersonal trust and commitment to collaboration as well as meaningful knowledge sharing and collaborative critical reflection (Wang & Lin, 2021). Relationships should be established at the onset of a collaborative learning task and nurtured throughout the learning process to enhance a sense of community (Brindley et al, 2009).…”
mentioning
confidence: 99%